Medical students’ attitudes towards healthcare for people with intellectual disabilities: an experience from Al-Jouf, Saudi Arabia - Adel Saber Alanazi (BMC Health Services Research)
Abstract This study examines the attitudes of medical students in the Al-Jouf region of Saudi Arabia and their potential influence on future healthcare delivery for people with intellectual disabilities (PwIDs). The research focuses on three fundamental concepts-ethical attitudes (EA), professional attitudes (PA), and social attitudes (SA)-to evaluate their direct role in determining healthcare quality. Furthermore, the study investigates the mediating functions of Knowledge Acquisition (KA) and Communication Skills (ComS). To assess the relationships between variables in a sample of 166 medical students, data were analyzed using descriptive statistics, hypothesis testing, and partial least squares structural equation modeling (PLS-SEM). The analysis suggests associations between medical students’ ethical, professional, and social attitudes and their potential approaches to future healthcare delivery for PwIDs. Knowledge Acquisition emerged as a significant mediating factor, while Communication Skills showed no significant mediating effect, possibly reflecting curricular gaps in communication training. These findings suggest several specific interventions: (1) integration of structured PwIDs-focused modules within medical curricula, emphasizing both theoretical knowledge and practical skills; (2) implementation of mandatory clinical rotations with PwIDs populations to enhance experiential learning; and (3) development of communication training programs focusing on patient-doctor and interprofessional interactions. The study suggests that policymakers and medical educators should set clear standards for disability skills in medical training, create ways to evaluate how well students care for PwIDs, and develop specific training programs for teachers.